Influence on the Carcass Yield of Native Chicken using Maggot as A Nutrient - Amizar, Robi; Haikal, Muhammad; Yuniza, Ahadiyah; Wizna (Andalasian Livestock, 2024)
This study aims to determine the effect of BSF (Black Soldier Fly) maggot in rations on native chicken carcass yield, including body weight, carcass weight, carcass percentage, and abdominal fat. The native chicken that was used in this study was KUB chicken. This study used 100 native chickens aged six weeks, and the study duration was six weeks. Chickens were placed in cages measuring 100×100×100 cm. The experimental method in this study included a completely randomized design (CRD) with five treatments and four replications. The treatment used treatment T1 (0% maggot flour), T2 (7% maggot flour), T3 (14% maggot flour), T4 (21% maggot flour), and T5 (28% maggot flour). The ration was prepared with 17.5% iso-protein and 2800 kcal/kg iso-energy. Body weight, carcass weight, carcass percentage, and abdominal fat percentage were observed in this study. The results and analysis of variance showed that the inclusion of BSF maggot flour in rations had a significant effect (P<0.05) on body weight and carcass weight, had no significant effect (P>0.05) on carcass percentage, and highly significant (P<0.01) to abdominal fat percentage. In conclusion, using up to 14% of BSF maggot flour produced the best carcass yield on the native chicken of KUB.